The lost glamur of pharmacy in Debeljača : Izgubljeni sjaj ljekarništva u Debeljači - Dželajlija, Darko D. (Array, 2021)
In the general trend of nationalization after 1945, many pharmacies in our area were destroyed, relocated or repurposed. During these events, their interiors changed, and the inventory was damaged or destroyed. The aim of this paper is to research the historiography of pharmacy by reconstructing the chronology of the Joanović pharmacy as well as the Public Pharmacy of the town of Debeljača until it moved out of the building where the pharmacy was founded. Descriptive research covers the periods before the First World War, between the two World Wars and after the Second World War. The data presented in this paper are the result of interdisciplinary research related to the study of the historiography of the Joanović pharmacy as well as the Public Pharmacy of the town of Debeljača. This paper is based on unpublished documents (database of the pharmacy Joanović and the Publik Pharmacy of the town of Debeljača), as well as on the statements and written statements of Mrs. Mile Đorđević born Joanović and pharmacist Ivan Šimić as documents from the author"s personal archive. Methods of documentation analysis and desk analysis of secondary data were used. In the Joanović Pharmacy, almost semi-industrial production of cosmetic and perfumery products was developed, as well as the production of flavors for the production of alcoholic and non-alcoholic beverages. After the forced purchase, a biochemical laboratory was formed in the newly established National Pharmacy, which provided a large number of various laboratory services. The results of this study could be used in further study of the historiography of pharmacy research of the goods that pharmacies offered to consumers.